Molecular complementation of a collagen mutation in mammalian cells using yeast artificial chromosomes. - Strauss, W M (1992)
The cloning of large contiguous segments of mammalian DNA in Saccharomyces cerevisiae has become possible with the advent of Yeast Artificial Chromosomes (YACs). We are interested in extending the technique of genetic complementation analysis to the molecular level through the introduction of YACs into mammalian cells and the mammalian germline. We report the successful introduction of homogeneous DNA derived from a 150 kbp YAC spanning the murine Col1a1 locus into murine fibroblasts carrying a mutation at this locus. The YAC DNA was fractionated by pulse field electrophoresis, condensed with polyamines, and introduced into mutant fibroblasts via DNA-lipid micelles. The DNA was integrated as a stable intact unit in 10% of the transfected clones conferring collagen RNA expression to the mutant cells.